Central nervous system infections in the absence of cerebrospinal fluid pleocytosis - Erdem, Hakan; Ozturk-Engin, Derya; Cag, Yasemin; Senbayrak, Seniha; Inan, Asuman; Kazak, Esra; Leblebicioglu, Hakan (Elsevier B.V., 2017)
Previous multicenter/multinational studies were evaluated to determine the frequency of the absence of cerebrospinal fluid pleocytosis in patients with central nervous system infections, as well as the clinical impact of this condition. It was found that 18% of neurosyphilis, 7.9% of herpetic meningoencephalitis, 3% of tuberculous meningitis, 1.7% of Brucella meningitis, and 0.2% of pneumococcal meningitis cases did not display cerebrospinal fluid pleocytosis. Most patients were not immunosuppressed. Patients without pleocytosis had a high rate of unfavorable outcomes and thus this condition should not be underestimated. © 2017 The Author(s)
Keywords: CSF; Encephalitis; Leukocyte; Meningitis; Pleocytosis